Successful pharmaco-invasive approach using a lower alteplase dose and VA-ECMO support in high-risk pulmonary embolism: case report - Gutierrez-Gallegos, Paola; Jimenez-Franco, Vicente; Jerjes-Sanchez, Carlos; Quevedo-Salazar, Renata; Rodriguez-Rivera, Jahir; Paredes-Gutierrez, Enrique; Lira-Lozano, Daniel; Quintanilla-Gutierrez, Juan; Gomez-Gutierrez, Rene; de la Peña-Almaguer, Erasmo; Torre-Amione, Guillermo (Frontiers in Cardiovascular Medicine, 2024)
Despite the elevated mortality rates associated with high-risk pulmonary embolism (PE), this condition remains understudied. Data regarding the effectiveness and safety of invasive therapies such as venoarterial extracorporeal membrane oxygenation (VA-ECMO) in this patient population remains controversial. Here, we present the case of a 61-year-old male with high-risk PE associated with refractory cardiac arrest and cardiogenic shock who underwent a combination of extracorporeal cardiopulmonary resuscitation with VA-ECMO and pharmaco-invasive therapy (mechanical thrombi fragmentation plus lower alteplase dose), resulting in successful pulmonary reperfusion. After a prolonged in-hospital stay, the patient was discharged in stable condition.